2007
DOI: 10.1111/j.1574-6968.2007.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliO157:H7 gene expression in the presence of catecholamine norepinephrine

Abstract: Various forms of host stresses (e.g. physiological, psychological) are thought to influence susceptibility to pathogenic microorganisms. Catecholamines such as norepinephrine are released into the GI environment during acute stress and may influence the infective process of bacterial pathogens associated with the GI tract. To examine the effects of norepinephrine on expression of virulence factors in Escherichia coli O157:H7, the clinical-type isolate EDL933 (ATCC 43895) was grown in serum-Standard American Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 65 publications
7
39
0
1
Order By: Relevance
“…Although variations in the methodologies used for the transcriptional profiling make direct comparisons between the studies difficult, overall the gene expression profiles obtained support the view that exposure to catecholamines enhances expression of genes involved in bacterial pathogenicity (such as motility, iron acquisition, and epithelial cell attachment) [12,17,25,51]. Interestingly, a very recent paper by Peterson et al showed in vitro that stress hormone exposure enhanced the horizontal gene transfer efficiencies of a conjugative plasmid from a clinical host strain of Salmonella Typhimurium to an E. coli recipient [52].…”
Section: Catecholamine Effects On Bacterial Virulencementioning
confidence: 72%
See 2 more Smart Citations
“…Although variations in the methodologies used for the transcriptional profiling make direct comparisons between the studies difficult, overall the gene expression profiles obtained support the view that exposure to catecholamines enhances expression of genes involved in bacterial pathogenicity (such as motility, iron acquisition, and epithelial cell attachment) [12,17,25,51]. Interestingly, a very recent paper by Peterson et al showed in vitro that stress hormone exposure enhanced the horizontal gene transfer efficiencies of a conjugative plasmid from a clinical host strain of Salmonella Typhimurium to an E. coli recipient [52].…”
Section: Catecholamine Effects On Bacterial Virulencementioning
confidence: 72%
“…In an attempt to define the global transcriptional response of bacteria to catecholamine exposure, a number of microarray studies have been undertaken [12,17,25,47]. Although variations in the methodologies used for the transcriptional profiling make direct comparisons between the studies difficult, overall the gene expression profiles obtained support the view that exposure to catecholamines enhances expression of genes involved in bacterial pathogenicity (such as motility, iron acquisition, and epithelial cell attachment) [12,17,25,51].…”
Section: Catecholamine Effects On Bacterial Virulencementioning
confidence: 85%
See 1 more Smart Citation
“…Without induction, two-thirds of the strains were identified as poor producers of Stx (0 to 1ϩ), but 99% of the strains were inducible for Stx2e production by mitomycin C. Mitomycin C was chosen as a potent inductor for phage-encoded gene expression in vitro. The inducibility of Stx production is likely to play a role in vivo for pathogenesis, since Stx production was shown to be triggered by neutrophils and norepinephrine in the gastrointestinal tract (13,49). The inducible phenotype could not be related to phage production (data not shown) or to the integrity of the phage P27 genome in these strains.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, Dowd carried out microarray analyses of E. coli O157:H7 virulence gene expression in the presence of NA (Dowd, 2007). He reported that E. coli O157:H7 grown in serum-containing culture medium containing NA showed differential regulation of 101 genes compared with similarly grown non-supplemented controls.…”
Section: Stress Hormone Modulation Of Bovine Enteropathogen Virulencementioning
confidence: 99%